MARKETING ANALYSIS AND MONITORING OF PRICES FOR MEDICATIONS WITH CORTICOSTEROIDS OF SOFT DOSAGE FORM USED IN DERMATOLOGY - Vons, B. V.; Chubka, M. B.; Hroshovyi, T. A. (Фармацевтичний часопис, 2016)
MARKETING ANALYSIS AND MONITORING OF PRICES FOR MEDICATIONS WITH CORTICOSTEROIDS OF SOFT DOSAGE FORM USED IN DERMATOLOGY B. V. Vons, M. B. Chubka, T. A. Groshovyi SHEI “Ternopil State Medical University by I. Ya. Horbachevsky” Summary: It was studied the assortment of soft medications with corticosteroids used in dermatology. It was found the correlation of domestic and foreign medications within each pharmacotherapeutic subgroup of medications. The price range was analyzed and the liquidity ratio for medications in this category was calculated too. Key words: corticosteroids, soft dosage forms, price monitoring, market research. Every year the level of skin disease is growing rapidly. Today soft medications (SM) take the first place for the local treatment of dermatological diseases [1, 2]. SM with corticosteroids (CS) are the most commonly used medications in dermatology. This group of medications (M) for over 50 years is used for treatment of dermatitis, eczema, erythema, psoriasis, for relieving symptoms of inflammation and itching of the skin. However, the price is one of the constituent elements of pharmaceutical marketing and one of the most important factors determining the choice of buyers and demand for goods [4]. The aim of research was to study the index of medication assortment with corticosteroids, summarize the results of price analysis, namely: the calculation of average retail prices of medications, liquidity ratios of prices, which were analyzed with the following justification of general trends. The object of the study was the information posted on the website “Regulatory and legislative documents of the Ministry of Health of Ukraine” [5] about registered SM in Ukraine and the method of analysis of used secondary marketing information. There has been 492 names registered, of which 226 medications are used in dermatology according to preliminary studies, for the date of January 1, 2015. The largest number of registered medicines belongs to the group of medications with corticosteroids (D 07), 80 medications are used in dermatology. According to the order No. 235 “classifier dosage forms” [7] of MPH of Ukraine, all registered medications with CS were divided due to their dosage form into creams, ointments, gels, pastes, liniments. Thus, in the ratio ointments and creams have 49.43 % of the assortment, gels only 1.15 % and corticosteroid medications such as liniments and pastes are not represented on the pharmaceutical market of Ukraine. The domestic market of SM with CS depends on import because soft dosage forms (SDF) of foreign manufacturing take 73.56 % of assortment, while soft dosage forms (SDF) of domestic production have 26.44 % of the market. SM with CS are represented by 12 countries of the world at Ukrainian market, the leaders are: Poland – 21.87 %, India – 14.06 %, Italy – 12.5 %, Germany – 10.93 %, Belgium and Croatia – 9,37 % each. In Ukraine, SM with corticosteroids are produced by 8 pharmaceutical enterprises of different ownership. Leading manufacturing positions are occupied by Pharmaceutical Company Zdoroviya, LLC – 26.08 %, Farmak, PJSC, Pharmaceutical company Darnytsiya, PJSC and Kievmedpreparat, PJSC have 17.39 % each of pharmaceutical market. Price is one of the most important elements of the marketing complex because it determines the monetary price paid for a particular product [8]. Price features of SDF with CS presented at the domestic wholesale market from January 2015 to May 2015 were investigated during the research. In particular, dynamics of changes, average weighted wholesale price and liquidity ratios were studied. Wholesale prices presented on an electronic resource “Ezhenedelnyk apteky” [9] were used for the analysis. We analyzed the pricing environment of SDF with CS and defined liquidity ratio, which has showed the balance between the maximum and minimum price of a particular medication at a current period at the appropriate market [4] for this category of medications of soft dosage form during January - May 2015. Аt 6.89 % of medications of soft dosage forms with CS have liquidity ratio less than 0,15, in 52.89 % of medications liquidity ratio range between 0,15-0,5, and 40.22 % of medications of soft dosage form with CS have liquidity ratio higher than 0,5. Also it was found the average arithmetic wholesale prices for this group of medications during the studied period. All SM with corticosteroids (group D 07 according to ATC classification) were analyzed due to the international non-patented name and divided into domestic and imported medications. Average price for 1 pack of medication of SDF with corticosteroids had a significant tendency to change a price during the period of study. The wholesale price of the medication with CS of domestic manufacturer varies from UAH 14.02 per pack to 67.43 UAH, while the price of imported medication is from 19.89 UAH to 267.35 UAH per one pack. It should be noted that the price of imported medications is higher in three times than the price of domestic counterparts. References Vons B. V. Market analysis of semisolid dosage forms registered in Ukraine and research of excipients included to their formulas / B. V. Vons, M. B. Chubka, T. A. Groshovyi // Farmatsevtychnyy chasopys. – 2015. – № 1. – P. 55-61. Analiz rynku zareyestrovanykh v Ukrayini m'yakykh likarsʹkykh zasobiv, yaki vykorystovuyutʹsya u dermatolohiyi / B. V. Vons, T. A. Hroshovyy, M. B. Chubka // Menedzhment ta marketynh u skladi suchasnoyi ekonomiky, nauky, osvity, praktyky: materialy III mizhnarodnoyi naukovo-praktychnoyi Internet-konferentsiyi, (26-27 bereznya 2015 r., m. Kharkiv). – KH.: Vyd-vo NFaU, 2015. – S. 303-304. Shmelʹkova K. S. Problema vyboru suchasnoho topichnoho hlyukokortykosteroyidy / Shmelʹkova K. S., Brykov O. L. // Mystetstvo likuvannya. – 2008. – N 8. – S. 114-116. Kosyachenko K. L. Naukovo-metodychni pidkhody do otsinky efektyvnosti systemy tsin na likarsʹki zasoby / K. L. Kosyachenko, A. S. Nemchenko, O. V. Kovalenko // Visnyk farmatsiyi. – 2010. – № 3. – S. 51-54. Normatyvno-dyrektyvni dokumenty MOZ Ukrayiny [Elektronnyy resurs] / Ministerstvo okhorony zdorovʺya Ukrayiny. – Rezhym dostupu do informatsiyi: http://mozdocs.kiev.ua/. Dovidnyk “Kompendium”. [Elektronnyy resurs]. – Rezhym dostupu do informatsiyi: http://compendium.com.ua/. Nakaz Ministerstva okhorony zdorov'ya Ukrayiny vid 26.06.2002 roku № 235 “Pro zatverdzhennya Klasyfikatora likarsʹkykh form” [Elektronnyy resurs] / Ministerstvo okhorony zdorovʺya Ukrayiny. – Rezhym dostupu do informatsiyi: .http://mozdocs.kiev.ua/view.php?id=1113. Myrzabekova M. YU. Mekhanyzm tsenoobrazovanyya v sovremennoy ékonomyke / M. YU. Myrzabeova // Ékonomyka y upravlenye v XXI veke: tendentsyy razvytyya. – 2013. – № 11. – S. 106-110. Ezhenedelʹnyk apteka. [Elektronnyy resurs]. – Rezhym dostupu do informatsiyi: http://pharmbase.com.ua/poisk.